Attitudes of owners and perspectives of sustainable tourist business in Vojvodina farms - Vesić Marina; Bogdanović Maja (Zbornik Radova: Geografski Fakultet Univerziteta u Beogradu)
Thinking sustainably and "green" through the activities of almost all organizations and companies, but also through personal attitudes and actions, has become an imperative of socially responsible business for those who deal with tourism and hospitality. There is an entrenched view that tourism should be viewed more broadly, i.e. as a system that, in addition to tourists and the economy, also includes the environment and society as a whole. Taking care of sustainable tourism development has become everyone's obligation ̶ both supply and demand. For the purposes of this research, the opinions of owners of Vojvodina salaš farms engaged in tourism and providing hospitality services were examined through a survey. The goal of the work is to determine, based on the presentation of various contents and activities on salaš farms (representation of ethnic complexes and accommodation facilities, organic food products, ecotourism activities, additional contents...) whether they respect the concept of sustainable development and whether they strive for it. Also, to answer the question whether traditional, but also "increasingly numerous" modern facilities on salaš farms contribute to the concept of sustainability? The analysis of the collected data was performed using the SPSS.26.00 statistical program, descriptive statistics were presented and One-way ANOVA was performed. The results of the research indicate a positive attitude of the respondents regarding the sustainable development of tourism, but also differences in their attitudes regarding the enrichment of the tourist offer on salaš farms with modern amenities.